Pengaruh Model Pembelajaran dan Intensitas Penggunaan Internet Terhadap Hasil Belajar Siswa pada Mata Pelajaran IPS Kelas VII di MTs Prima Bekasi - Muhammad Farhan Pratama; Uza Sukmana; Dahlan (Ekopedia: Jurnal Ilmiah Ekonomi, 2025)
This study aims to examine the influence of learning models and the intensity of internet use on student learning outcomes in the subject of social studies in grade VII of MTs Prima Bekas. This study uses a quantitative approach with a pre-experimental methodology. The research sample consisted of 30 grade VII students taken through a total sampling technique. Data collection instruments used questionnaires and documentation of student achievement score. The results of the study showed that: (1) learning methods did not have a significant effect on students' academic achievement (sig = 0.226); (2) the frequency of internet use had an influence but was not statistically significant on students' academic achievement (sig = 0.087); and (3) learning methods and frequency of internet use simultaneously did not have a significant effect on students' academic achievement (sig = 0.181). The coefficient of determination (R Square) value of 0.015 indicated that only 1.5% of the variation in students' academic achievement could be explained by these two variables. Thus, there are other elements outside of learning methods and frequency of internet use that also have the potential to influence the academic achievement of social studies student